HUBUNGAN JUMLAH LEUKOSIT DAN PERSENTASE LIMFOSIT TERHADAP TINGKAT DEMAM PADA PASIENANAK DENGAN DEMAM TIFOID DI RSUD BUDHI ASIH TAHUN 2018 - OKTOBER 2019 - Sarah Khairunnisa, (2020)
Typhoid fever is a systemic infectious disease characterized by patients experiencing fever due to the spread of Salmonella bacteria. Risks factor for typhoid fever are improper sanitation and hygiene. Leukopenia and lymphocytosis are relatively strong indication when someone has typhoid fever, both of which are thought to affect the fever levels of patients with typhoid fever. This study was conducted to determine the association of leukocyte count and the percentage of lymphocyte to the level of fever in pediatric patients with typhoid fever in RSUD Budhi Asih. The type of this research is an analytical observational studies with cross-sectional approach with a sample of 42 pediatric patients aged 8-14 years, the sample of this research are medical record data with a sampling technique in the form of purposive sampling. The age range of children with typhoid fever are mostly at 8 - 10 years 7 months old (57,1%). Based on gender, the highest prevalence occurs in women (61,9%). The result of this study shows that sample with normal leukocyte count, has a mild fever (93,3%) and sample with normal percentage of lymphocyte, has a mild fever (71,4%). Based on result of bivariate analysis with Chi-Square test, there is a significant association between the leukocytes count (p=0,004) to the levels of fever in pediatric patients with typhoid fever, whereas there is no significant association between the percentage of lymphocytes (p=0.277) to the levels of fever in pediatric patients with typhoid fever.